The assessment of the large flood impact on the microelements content in alluvial soils in the Amur river middle stream - A. V. Martynov (Бюллетень Почвенного института им. В.В. Докучаева, 2018)
The content of microelements is determined within the alluvial soils of the flood plain situated near the river bed in the middle flow of Amur River. The impact of the catastrophic flood of 2013 on their content is also revealed. The microelements were determined by using mass spectrometry in samples collected from genetic horizons. The principal component analysis has been applied to characterize the relationship between microelements, alluvial soil properties and macroelements composition. The associations of accumulation (Rb, Sr, Ba) and association of dispersion (Zr, Ta), having a lithogenic nature, are separated. The content of other microelements is lower than the average one for the world's soils. However, their concentration increases as the distance from the river bed increased. It is revealed that trace elements under the impact of flood waters are not accumulated only. They are also leached. Their migration is influenced significantly by floodplain topography: microelements are more affected to washing out in soils which are located near the river bed. Other factor which affects the microelements migration is the soil properties. Some microelements (Sr, Cd, Ba, Pb) are washed out from all types of soils. While the other ones (Y, Sc and Cr) are accumulated only. Flood affected greatly Mo (+43% average for the soil), Sc (+38%), Cu (+27%), Cd (-23%), Pb (-12%) and Sr (-12%). However, before the flood, significant correlation between microelements were observed only for exchangeable manganese and oxides aluminum and magnesium. Significant correlation between texture, organic matter and soil pH appeared after a long flood in all studied soils. These changes are probably caused by a decrease in the redox potential during flooding and the washing out of calcium oxide.